Pengaruh Brand Image, Brand Trust, Brand Satisfaction terhadap Brand Loyalty Pada E-Wallet Gopay - Selvia; Rusdi Hidayat Nugroho (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Brand Loyalty is a commitment that arises from consumers to a specific brand. Brand satisfaction, brand image, and brand trust are some of the variables that might impact brand loyalty. Non-cash payment via digital systems, which are an addition to e-commerce, refer to smart payment alternatives in several developing countries, one of which is indonesia. The emergence of digitalization through the Internet has accelerated the flow of globalization and payment systems from manual to online transactions. This research aims to determine the impact of brand image, brand trust, and brand satisfaction either concurrently or partially on the brand Loyalty of gopay e-wallet customers among UPN Veteran Jawa Timur. This kind of study employs quantitative associative research methodology. techniques and This study used 200 as the sample. respondents and used is a Google form. The collected data were analyzed using the Statistical Package for Social Sciences (SPSS). As a result, Brand Image, Brand Trust and Brand Satisfaction simultaneously influence the Gopay E-wallet Brand Loyalty. Based on the results of the t test, which are 111,361 > 2,65, the F test, it is known that brand loyalty is positively and significantly impacted by brand image (significantly significant effect = 0.000), positively and significantly impacted by brand trust (significant impact = 0.088), and positively and significantly impacted by brand satisfaction (significant impact = 0.004). the conclusion of this research is that Brand image, brand trust, brand satisfaction simultaneously influence the gopay e-wallet brand loyalty. Brand image has a positive and significant effect on brand loyalty. Brand trust has a positive and significant effect on brand loyalty